Mathematical Reasoning Abilities of High School Students in Solving Contextual Problems - Ainun Rahma Firdausy; Triyanto; Diari Indriati (GoAcademica Research & Publishing, 2021)
The purpose of this study was to describe students’ mathematical reasoning abilities, such as: drawing conclusions from a statement, doing mathematical manipulation, providing valid arguments and presenting mathematical statements, both verbally and in writing, in the form of pictures or graphs. This research used the descriptive qualitative method. The instruments used in this study were the main instrument (researchers) and the supporting instruments (tests and interviews). The test was given to 25 students of class XII SMA Muhammadiyah Surakarta Special Program (Muhammadiyah Surakarta Senior High School Special Program). The subjects of this study were eight students of class XII who were selected by purposive sampling technique. The results showed that students had good mathematical reasoning skills while doing mathematical manipulations and presenting mathematical statements verbally, in writing, or in pictures. Students did not show good mathematical reasoning skills when students have to draw conclusions from a statement and provide valid arguments. This is because students still do not master how to identify and determine the right strategy to solve problems, and the answers given by students were still not correct. In the future, teachers are expected to provide problems (questions) in various mathematical reasoning, so students are accustomed to working on problems with various levels of mathematical reasoning, and students’ mathematical skills can be better trained.